Studies of microwave characteristics and plasma parameters in low pressure discharge initiated in coaxial waveguide by stochastic radiation - Karas, V.I.; Alisov, А.F.; Golota, V.I.; Yegorov, А.М.; Karas, I.V.; Karelin, S.V.; Zagrebelny, I.А. (Вопросы атомной науки и техники, 2015)
The research methods are described and the principal characteristics of the generated oscillations are studied. We study the plasma discharge, initiated by microwave radiation with stochastically jumping phase (MWRSJP) in a coaxial waveguide at the optimal mode of the beam-plasma generator. Present results continue the line of the previous research. In this paper the plasma parameters of a microwave discharge at its stable maintenance in air by MWRSJP, and the pressure range at which required power is minimal are measured. We experimentally examine also optical characteristics of the discharge plasma in a wide range of air pressure. Описано методи дослідження і вивчені основні характеристики генерованих коливань. Вивчєно плазму розряду, ініційованого мікрохвильовим випромінюванням зі стохастичними стрибками фази (MХВССФ) у коаксіальному хвилеводі в оптимальному режимі роботи пучково-плазмового генератора. Знайдено параметри плазми мікрохвильового розряду при його стабільному підтриманні в повітрі МХВССФ та діапазон тисків, при якому споживана потужність мінімальна. Експериментально досліджено також оптичні характеристики плазми розряду в широкому діапазоні тисків повітря. Описаны методы исследования и изучены основные характеристики генерируемых колебаний. Изучена плазма разряда, инициированного микроволновым излучением со стохастическими скачками фазы (MВИССФ) в коаксиальном волноводе в оптимальном режиме работы пучково-плазменного генератора. Найдены параметры плазмы микроволнового разряда при его стабильном поддержании в воздухе МВИССФ и диапазон давлений, при котором потребляемая мощность минимальна. Экспериментально исследованы также оптические характеристики плазмы разряда в широком диапазоне давлений воздуха.